Influence of the equivalence ratio on the knock and performance of a hydrogen direct injection internal combustion engine under different compression ratios. (23rd March 2021) - Li, Yong; Gao, Wenzhi; Zhang, Pan; Fu, Zhen; Cao, Xingda
Abstract: Hydrogen has become an ideal alternative fuel for internal combustion engines. However, with an increase in the equivalence ratio and compression ratio, knock combustion is more likely to occur, which limits its engineering application. In this study, the effects of the equivalence ratio on the knock under different compression ratios were studied through numerical simulation. The signal energy ratio (SER) were used to evaluate the knock onset (KO). The knock intensity (KI) and engine performance were compared and analyzed under different equivalence ratios and compression ratios. The results revealed that a high compression ratio can significantly amplify the effect of the equivalence ratio on combustion and knock. Under the compression ratio of 17.5, KI increases more quickly, with the constant equivalence ratio rise and is more sensitive to ignition timing with equivalence ratio increasing. For the compression ratio of 11, the ignition timing limited by knock is about 4°CA earlier than that of compression ratio of 17.5, and the engine performance is more stable in the low-knock zone. However, when KI exceeds 1 MPa, the power and ITE decreases 20.6% and 20.9% respectively. Graphical abstract: Image 1 Highlights: The knock onset can be detected with signal energy ratio method in hydrogen ICE. A high compression ratio can amplify the effect of the equivalent ratio on knock. Knock intensity is more sensitive to spark timing with equivalence ratio rise. The performance is more stable in the low-knock zone under a low compression ratio.